Transition metal (Rh and Fe) complexes and main-group (Se and B) adducts with N, N′-diphosphanyl NHC ligands: a study of stereoelectronic properties. Issue 11 (11th February 2016) - Ai, Pengfei; Danopoulos, Andreas A.; Braunstein, Pierre
Abstract : The reactions of N, N ′-bis(di- tert -butylphosphanyl)-imidazole-2-ylidene (PCNHC P ) with [Rh(μ-Cl)(COD)]2, [Rh(μ-Cl)(CO)2 ]2, [Fe4 Cl8 (THF)6 ], elemental Se and [(C6 F5 )BO]3, have been investigated to evaluate the stereoelectronic properties of this hybrid ligand. Abstract : Attempts to evaluate experimentally the donor characteristics of the N, N ′-bis(di- tert -butylphosphanyl)-imidazole-2-ylidene (PCNHC P ) hybrid ligand are described. Thus, reactions ofPCNHC P with [Rh(μ-Cl)(COD)]2 and [Rh(μ-Cl)(CO)2 ]2 led to the formation of the mononuclear and dinuclear complexes, [Rh(PCNHC P, κ P, κ C NHC )2 ]Cl (PCNHC P-RhCl ) and [Rh(CO)(PC NHC, κ P, κ C NHC, κ N )]2 (PCNHC -RhCO ), respectively, the latter resulting after in situ cleavage of one ( t -Bu)2 P–Nimid bond ofPCNHC P . With ligands acting as a P, C-chelate, a straightforward evaluation of the Tolman electronic parameter (TEP) of the CNHC donor is problematical; the viability of dangling P- and bound CNHC -donors ( i.e. κ C NHC ) has been observed in the trinuclear Fe(ii ) chain complex [Fe3 Cl2 (μ-Cl)4 (THF)2 (PCNHC P, κ C NHC )2 ] (PCNHC P-Fe ), obtained by the reaction ofPCNHC P with [Fe4 Cl8 (THF)6 ] and, recently, established on Cr II, Co II and Au I centres. Evaluation of the π-accepting properties of thePCNHC P (and the relatedDipp-PCNHC ) was based on the 77 Se NMR chemical shifts of the corresponding NHC–Se adducts, PCNHC P-Se (andDipp-PCNHC -Se ), which were prepared from the freePCNHC P (andDipp-PCNHC ) and Se. The π-acidity ofPCNHC P is found to be higher than that ofDipp-PCNHC but lower than that ofSIPr . The donor ability of the CNHC inPCNHC P was explored by its reaction with the Lewis acids tris(pentafluorophenyl)borane (B(C6 F5 )3 ) and tris(pentafluorophenyl)boroxine ([(C6 F5 )BO]3 ), which resulted in stable donor–acceptor adducts with no FLP reactivity. The steric properties ofPCNHC P andDipp-PCNHC are conformation dependent, with the percent buried volume (% V bur ) ofPCNHC P in the structurally characterised conformer calculated at 67.6, the largest value currently reported for NHC ligands.